2022
DOI: 10.1186/s12903-022-02262-7
|View full text |Cite
|
Sign up to set email alerts
|

Retention of bar clip attachment for mandibular implant overdenture

Abstract: Objectives The aim of the present study was to evaluate the retention and loss of retention after fatigue testing at different time intervals between two types of bar clip materials (digitally designed PEEK bar clip and regular Nylon bar clip). Materials and methods An epoxy model was constructed for a completely edentulous mandible. Two implants were placed according to prosthetically driven implant placement by a computer-guided surgical stent. B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 33 publications
0
9
0
Order By: Relevance
“…The advancement of digital dentistry and computer-aided design and computer-aided manufacturing (CAD-CAM) technology made the attachments and retentive inserts design simpler with nearly flawless outcomes 21 . The digitally designed PEEK bar, PEEK and zirconia clip were chosen as they might provide perfect results in implant retained overdentures.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The advancement of digital dentistry and computer-aided design and computer-aided manufacturing (CAD-CAM) technology made the attachments and retentive inserts design simpler with nearly flawless outcomes 21 . The digitally designed PEEK bar, PEEK and zirconia clip were chosen as they might provide perfect results in implant retained overdentures.…”
Section: Discussionmentioning
confidence: 99%
“…A study evaluating the retention of these two types of bar clip materials after 3 years of simulated usage found that both materials offered good retention, with PEEK clips showing a decrease in retention by 58.66% and Nylon clips showing an increase in retention by 2.99%. Overall, the materials used for the construction of clips in bar-retained mandibular overdentures can vary, but both PEEK and Nylon have been shown to offer good retention for up to 3 years of use 20,21 .…”
Section: Mandibularmentioning
confidence: 99%
See 1 more Smart Citation
“…Inter group comparison of both situations was done as well. Pick up of the bar clips in the reinforced over denture base was made using autopolymerizing acrylic resin [ 38 ].…”
Section: Methodsmentioning
confidence: 99%
“…The importance of attachment design and manufacturing material selection cannot be overstated, as the use of attachments with suboptimal design or inappropriate materials can result in reduced retention and negatively impact periodontal support tissues [ 11 , 12 ]. Notably, the addition of clasp arms to movable dentures may enhance retention force, but requires experimental investigation to determine appropriate prosthetic materials and to obtain guidance for clinical design through experimental research.…”
Section: Introductionmentioning
confidence: 99%